New Polymer Materials Enable a Variety of Flexible Substrates. Issue 4 (1st July 2017) - Voutsas, Tolis; Reit, Radu; Avendano, Adrian; Arreaga, David; Dupree, John
Abstract : The Pylux family of polysulfide thermosetting polymers (PSTs) has been developed to enhance manufacturing options for a wide range of flexible displays and electronics.